Developing Set of Word Senses of Vocabulary in Al-Qur’an - Aqila, Neca; Bijaksana, Mochammad Arif (Universitas Hamzanwadi, 2020)
Al-Qur’an has become the guideline for all Muslims in the world, which makes many Muslims are eager to understand its contents. Nevertheless, Al-Qur’an consist of many words that have more than one meaning, which represent certain difficulties while understanding the meaning itself. As example, the word أَزْوَاجًا has two equivalents as it might be translated either